Decision‐making in an inquisitorial system: Lessons from Brazil. Issue 1 (13th February 2022) - Ribeiro, Ludmila; A. Diniz, Alexandre M.; Bastos Lages, Lívia
Abstract: This paper seeks to understand how decision‐making works at the first appearance hearings (Custody Hearings) in Brazil, an initiative that intends to make the Brazilian criminal justice system more accusatorial. We used primary data gathered in the hearings between April and December 2018 in nine Brazilian states. Binary logistic regression models were applied to identify the variables that affect the odds ratios of pretrial detention. Results indicated a high level of homology between the prosecutors' requests and the judges' decisions, even when controlling for the characteristics of offense and offender, which precludes any direct openness to the defense. Decision‐making in the Custody Hearing reinforces the inquisitorial characteristics and the institutional features of the Brazilian Criminal Justice System, suggesting that the reforms carried out over the last years were not able to change how actors operate on a daily basis.